أثر الاغتراب الوظيفي على كفاءة الأداء المؤسسي من منظور الإدارة الإسلامية: دراسة تحليلية على مجلس الدولة، والشورى في سلطنة عُمان: THE IMPACT OF CAREER ALIENATION ON THE EFFICIENCY OF INSTITUTIONAL PERFORMANCE FROM THE PERSPECTIVE OF ISLAMIC MANAGEMENT: AN ANALYTICAL STUDY OF THE COUNCIL OF STATE AND THE SHURA COUNCIL IN OMAN. - Khalfan bin Nasser AlYahyaei, Fahad bin; Muwazir , Mohd Rizal bin; Khan, Issa (Online Journal of Islamic Management and Finance (OJIMF), 2022)
The study aimed to measure the impact of job alienation on the efficiency of institutional performance from the perspective of Islamic management among the employees of the State Council and the Shura Council in the Sultanate of Oman. The problem of the study lies in measuring the impact of job alienation on the efficiency of institutional performance from the perspective of Islamic management, and in diagnosing the existence of the phenomenon of job alienation among the study sample, and the extent of its impact on institutional performance, due to the low application of the principles of management adopted in modern and Islamic management sciences in some administrative transactions, which can sense many problems facing the employee in general in government institutions and in the State Council and the Shura in particular, and the significance of the study lies in helping top management in understanding the psychological and moral aspect and how to deal with it by knowing the great impact of job alienation with all its elements. The study population will be the staff of the State Council and the Shura in the Sultanate of Oman, whereas the study sample was chosen by the stratified random method. The sample consisted of the category of employees occupying permanent jobs in the upper, middle and administrative levels, which are (375) from the total population of the research sample. The study variables are as follows, the independent variable is job alienation, represented by (lack of power, functional isolation, and self-alienation), the dependent variable is the efficiency of institutional performance, represented by (self-confidence, perfect work completion, effective social communication), and there is the axis of Islamic management. And the mediating variable is (type, institution, educational qualification, years of experience, and administrative level). The study will follow an analytical descriptive approach to describe and analyze the phenomenon of job alienation, and rely on the quantitative approach through the questionnaire survey. The pilot test will distribute to (40 samples), and the influence of the study variables (ID & DV) will be verified through the "Islamic management" axis.